Exploring Technology Integration in Islamic Character Education: Perspectives from Early Childhood Education - Deni Febrini; Aziza Aryati; Nova Asvio; Wifqo Arova Syams (CV FOUNDAE, 2024)
This study arises from the pressing need to incorporate technology within the framework of Islamic character education at Permata Bunda Early Childhood Education (PAUD), a domain that has received limited attention. As a response, this research seeks to make a meaningful contribution by promoting technology-driven approaches in early childhood education. This study aims to explore the impact of online learning media on the development of Islamic character in students at Permata Bunda PAUD, Bengkulu City. Employing a qualitative approach and a case study method, the research involves students, teachers, and parents as subjects to understand the dynamics of applying online media in Islamic character education. The findings indicate that online learning media, such as interactive videos, Islamic songs, and religious education applications, positively contribute to instilling values of honesty, discipline, compassion, and responsibility in students. However, its implementation has significant challenges, including limited technological infrastructure, teacher competency, and parental involvement. This study underscores the importance of collaboration among teachers, parents, and educational technology developers to maximize the benefits of online media in Islamic character education. Recommendations are made to enhance teacher competency, provide technological infrastructure, and involve parents in supporting the learning process.